Design parameters affecting mechanical failure and electrochemical degradation of ultrathin Li-ion pouch cells under repeated flexing - Kim, Kyungbae; Chan, Candace K. (Frontiers in Batteries and Electrochemistry, 2024)
Understanding mechanical failure modes of Li-ion battery electrodes of varying sizes and capacities is crucially important for the development of mechanically robust and high energy density flexible lithium-ion batteries (FLIBs). Three types of pouch cells (nominal capacities of 15, 25, and 50 mAh) were examined to understand how various design features used in the cells affected their mechanical failure modes and electrochemical performance after repeated introduction of compression and tension during bending. Postmortem microstructure analysis was carried out to identify the impacts of repeated flexing; several failure modes such as crack propagation, particle detachment, composite delamination, separator damage, electrode tears, and micro-short circuits were observed. We find that the observed mechanical failure modes are mainly dependent on the: 1) size and shape of the electrode composite materials, 2) configuration of the components within the cell (e.g., method of electrode folding, location of welded tabs), and 3) orientation of the long axis of the cell with respect to the bending axis. It was observed that the discharge capacity for all cell types studied herein was only slightly decreased (∼6–7% at 2C-rate) even after 3,000 repeated bends at a 25 mm radius of curvature provided if the bending axis is aligned to the long dimension of the cell. The results of this study provide valuable information on possible failure modes in Li-ion battery electrodes subjected to repeated flexing and how they can be mitigated to improve the dependability of practical pouch cells for FLIBs.